Why occupy République? Redefining French citizenship from a Parisian square - Hancock, Claire (Documents d’Anàlisi Geogràfica, 2017)
This paper discusses the recent occupation of the place de la République of Paris by the Nuit Debout movement, working with the assumption that it casts light on the shortcomings of French republican citizenship. Starting with the premise that space matters, it examines the major redevelopment project that the square underwent between 2008 and 2013, reflecting on the possible relation with the gentrification of the Eastern neighbourhoods of Paris. The paper then draws on what is known of the participants in the Nuit Debout movement to question its attempts, but ultimate failure, to fully include figures that were alien to the archetype of the French citizen, women, and people of colour. Despite efforts made to overcome the centralized nature of the movement and to reach out to the concerns of working-class peripheral neighbourhoods, the highly symbolic and central space of the place de la République spatially embodied the exclusionary nature, and violence, of the French public sphere.